A Test of Market Efficiency: Evidence from the Icelandic Stock Market - Stefán B. Gunnlaugsson 1970- (Viðskiptadeild Háskólans á Akureyri, 2005)
This extensive study examines the relationship between the price-to-earnings (P/E) ratio, the market-to-book (M/B) ratio, dividend yields, size, past returns, and current returns of Icelandic stocks. The study uses monthly return data on stocks from the Iceland Stock Exchange from January 1993 to June 2003. The model, which uses multiple regression analysis with dummy variables, is based on the classical Capital Asset Pricing Model, so the beta coefficient is the sole measure of risk. The findings are that the returns of stocks with a low P/E ratio are much higher than returns of other stocks, and that these returns are statistically significantly higher when differences in systematic risk are accounted for. The returns of small stocks and stocks with a low M/B ratio are higher than that of other stocks but the difference is not statistically significant. However, there is no relationship between current returns and historical returns, or between returns and dividend yields. JEL classification: G12 Keywords: Market efficiency, Icelandic stock market, P/E ratio